1973
DOI: 10.1070/qe1973v002n04abeh004456
|View full text |Cite
|
Sign up to set email alerts
|

OPTICAL ABSORPTION SPECTRUM OF EXCITED Cr3+IONS IN YTTRIUM ALUMINUM GARNET

Abstract: We show that the Wigner fuction of a cavity field can be constructed from the spontaneous emission spectrum in driven three-level atomic systems. We consider two configurations, the upper-and lower-level couplings, in which the driving field is the quantized field inside a cavity. In the proposed method, the Wigner function of the driving field is recovered in a straightforward manner, without much mathematical manipulation of the experimental data, from the spontaneous emission spectra.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 1 publication
(1 reference statement)
1
11
0
Order By: Relevance
“…5 shows typical excitation and emission spectra in the system Y 3 Al 5 À y O 12 :yCr 3 + , which are in reasonable accordance with the single crystal data reported in Ref. [5]. The features of the spectra are quite similar to those of Al 2 O 3 :Cr 3 + , in which Cr 3 + replaces Al at octahedral site, thus the spectra can be understood by the Tanabe-Sugano diagram for d 3 configuration in octahedron [6].…”
Section: Luminescent Properties Of Ce 3 + or Cr 3 + Singly Doped Y 3 supporting
confidence: 87%
See 2 more Smart Citations
“…5 shows typical excitation and emission spectra in the system Y 3 Al 5 À y O 12 :yCr 3 + , which are in reasonable accordance with the single crystal data reported in Ref. [5]. The features of the spectra are quite similar to those of Al 2 O 3 :Cr 3 + , in which Cr 3 + replaces Al at octahedral site, thus the spectra can be understood by the Tanabe-Sugano diagram for d 3 configuration in octahedron [6].…”
Section: Luminescent Properties Of Ce 3 + or Cr 3 + Singly Doped Y 3 supporting
confidence: 87%
“…At this stage, we cannot give firm assignments for the weak emission peaks at 671, 706 and 723 nm. Sevast'yanov et al indicated that these emissions were from electron-vibrational transitions [5]. Accurate analysis was conducted, indicating that the sharp line emission at 693 nm was from the minor impurity phase Al 2 O 3 :Cr 3 + .…”
Section: Luminescent Properties Of Ce 3 + or Cr 3 + Singly Doped Y 3 mentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 4 shows the PLE and PL spectra of a selected Cr 3þ singly doped sample MgSrAl 9.95 O 17 :0.05Cr 3þ . The features of the spectra are quite similar to those of Al 2 O 3 :Cr 3þ , 12 in which Cr 3þ replaces Al at octahedral site, thus the spectra of MgSrAl 9.95 O 17 :0.05Cr 3þ z E-mail: xiazg@cugb.edu.cn; xpjing@pku.edu.cn can be understood by the Tanabe-Sugano diagram for d 3 configuration in octahedron. 6 Under excitation at 400 and 560 nm, the emissions of Cr 3þ are observed in the deep-red region.…”
Section: Resultsmentioning
confidence: 86%
“…[ 12 ] For previously reported Cr 3+ activated garnet phosphors, there are two major drawbacks to be resolved: one is the low absorption efficiency (AE) of Cr 3+ in the high‐symmetry octahedral sites of those garnet hosts; another is the reduced IQE when λ em,max > 800 nm. [ 6,13 ] Here, we report a new broadband NIR garnet phosphor Lu 2 CaMg 2 Ge 3 O 12 :Cr 3+ (LCMG:Cr 3+ ), where the cation disordering in the dodecahedral sites allows for octahedrally coordinated Cr 3+ without the inversion symmetry to achieve high AE and concentration‐dependent PL properties. Furthermore, we demonstrate that the introduction of Yb 3+ into LCMG:Cr 3+ not only substantially increases the overall FWHM from 152 to 262 nm, but also simultaneously improves the IQE and thermal stability.…”
Section: Introductionmentioning
confidence: 99%